KONSEP TA’LĪM AL-MUTA’ALLIM DALAM KULTUR ADAB PERGURUAN TINGGI ISLAM DI KALIMANTAN SELATAN - Samdani Samdani; Isny Lellya (UIN Antasari Banjarmasin, 2021)
Using a descriptive qualitative approach, this study seeks to reveal the basic framework of the culture of manners in Islamic universities in South Kalimantan, especially in the three Islamic Colleges in South Kalimantan. The adab was analyzed by pivoting on the values in the Ta'līm al-Muta'allim book. The results of this study also revealed comprehensively the perceptions of lecturers and students on manners in the learning process, the values of adab were analyzed using a value analysis approach using data collection techniques, interviews, surveys and observations. Based on the research results, it was indintified that the values of adab and the way of thinking of lecturers and students in the learning process are in accordance with the values of adab as stated in the Ta'līm al-Muta'allim book. The awareness to implement certain adab was based on the goals to be achieved in the learning process or in the framework of seeking knowledge. Adab also takes place in certain dimensions, such as adab to Allah and the Prophet (spiritual attitude dimension) which is the core and basis of other dimensions; adab to humans (integration of the dimensions of spiritual and social attitudes); adab to oneself and to fellow humans (integration of the dimensions of spiritual & social attitudes). Some of the values implemented in the learning process could be seen in the doctrinal process of seeking knowledge conveyed by several lecturers to students, lecturers 'exposure to students regarding the virtues of studying, the students' intentions to study, the way students chose friends in association, how the students respected the lecturers, time management in learning, and some implementation of values that were in line with what was stated in the Ta'līm al-Muta'allim book.Kajian lapangan dengan pendekatan kualitatif dan metode deskriptif ini berupaya mengungkapkan kerangka dasar budaya adab yang berlangsung di perguruan tinggi Islam di Kalimantan Selatan, khususnya di tiga Sekolah Tinggi Agama Islam yang ada di Kalimantan Selatan. Adab tersebut dianalisis dengan kacamata nilai-nilai yang tertuang dalam kitab Ta’lîm al-Muta’allim. Selain itu, hasil penelitian ini juga mengungkapkan secara komprehensif mengenai persepsi dosen dan mahasiswa mengenai adab dalam proses pembelajaran, nilai-nilai adab tersebut dianalisis dengan pendekatan analisis nilai dengan menggunakan teknik mengumpulan data wawancara, survei, dan observasi. Berdasarkan hasil penelitian diketahui bahwa nilai-nilai adab dan cara berfikir dosen dan mahasiswa dalam proses pembelajaran dan pembelajaran sangat sesuai dengan nilai-nilai adab yang tertuang dalam kitab Ta’lîm al-Muta’allim. Kesadaran untuk mengimplementasikan adab tertentu didasari pada tujuan yang hendak dicapai dalam proses pembelajaran atau dalam kerangka mencari ilmu pengetahuan. Adab juga berlangsung dalam dimensi-dimensi tertentu, seperti adab kepada Allah dan Nabi (dimensi sikap spiritual) yang menjadi inti dan dasar dimensi lainnya; adab kepada manusia (integrasi dimensi sikap spiritual dan sosial); adab kepada diri sendiri dan kepada sesama manusia (integrasi dimensi sikap spiritual dan sosial). Adapun beberapa nilai yang terimplementasikan dalam proses pembelajaran dapat terlihat dalam proses doktrin tentang hukum mencari ilmu yang disampaikan oleh beberapa dosen kepada mahasiswa, adanya pemaparan dosen kepada mahasiswa terkait keutamaan menuntut ilmu, niat para mahasiswa menuntut ilmu, cara para mahasiswa dalam memilih sahabat dalam pergaulan, cara para mahasiswa menghormati dosen, pengaturan waktu dalam belajar, dan beberapa implementasi nilai yang sejalan dengan apa yang tertuang dalam kitab Ta’lîm al-Muta’allim.